Phosphoproteomic screening identifies Rab GTPases as novel downstream targets of PINK1. (16th October 2015) - Lai, Yu‐Chiang; Kondapalli, Chandana; Lehneck, Ronny; Procter, James B; Dill, Brian D; Woodroof, Helen I; Gourlay, Robert; Peggie, Mark; Macartney, Thomas J; Corti, Olga; Corvol, Jean‐Christophe; Campbell, David G; et al.
Abstract: Mutations in the PTEN‐induced kinase 1 (PINK1) are causative of autosomal recessive Parkinson's disease (PD). We have previously reported that PINK1 is activated by mitochondrial depolarisation and phosphorylates serine 65 (Ser 65 ) of the ubiquitin ligase Parkin and ubiquitin to stimulate Parkin E3 ligase activity. Here, we have employed quantitative phosphoproteomics to search for novel PINK1‐dependent phosphorylation targets in HEK (human embryonic kidney) 293 cells stimulated by mitochondrial depolarisation. This led to the identification of 14, 213 phosphosites from 4, 499 gene products. Whilst most phosphosites were unaffected, we strikingly observed three members of a sub‐family of Rab GTPases namely Rab8A, 8B and 13 that are all phosphorylated at the highly conserved residue of serine 111 (Ser 111 ) in response to PINK1 activation. Using phospho‐specific antibodies raised against Ser 111 of each of the Rabs, we demonstrate that Rab Ser 111 phosphorylation occurs specifically in response to PINK1 activation and is abolished in HeLa PINK1 knockout cells and mutant PINK1 PD patient‐derived fibroblasts stimulated by mitochondrial depolarisation. We provide evidence that Rab8A GTPase Ser 111 phosphorylation is not directly regulated by PINK1 in vitro and demonstrate in cells the time course of Ser 111 phosphorylation of Rab8A, 8B and 13 is markedly delayed compared to phosphorylation of Parkin at Ser 65 . We further show mechanistically that phosphorylation at Ser 111 significantly impairs Rab8A activation by its cognate guanine nucleotide exchange factor (GEF), Rabin8 (by using the Ser111Glu phosphorylation mimic). These findings provide the first evidence that PINK1 is able to regulate the phosphorylation of Rab GTPases and indicate that monitoring phosphorylation of Rab8A/8B/13 at Ser 111 may represent novel biomarkers of PINK1 activity in vivo . Our findings also suggest that disruption of Rab GTPase‐mediated signalling may represent a major mechanism in the neurodegenerative cascade of Parkinson's disease. Synopsis: The Parkinson's disease‐mutated PINK1 kinase phosphorylates Parkin and ubiquitin. Phosphoproteomic screening reveals Rab8A, Rab8B and Rab13 GTPases as some of only few additional targets whose phosphorylation depends on PINK1 during mitophagy. Activated PINK1 indirectly controls phosphorylation of serine 111 of Rab8A and closely related Rab GTPases. Biochemical and cellular analysis imply an unknown intermediate PINK1‐dependent Rab8A Ser111 kinase or phosphatase. PINK1‐directed activation of Parkin E3 ligase activity is independent of Rab8A Ser111 phosphorylation Phosphorylation at Ser111 inhibits Rab8A activation by its guanine exchange factor, Rabin8. Abstract : Ser111 modification of Rab8A, Rab8B and Rab13 represent some of only few PINK1‐dependent phosphorylation events and may regulate GTPase function during mitophagy.